Additional records of Neopsittaconirmus lice (Insecta: Phthiraptera: Ischnocera) parasitizing captive parrots - Oniki-Willis, Yoshika; Sychra, Oldrich; Palma, Ricardo Luis (Revista brasileira de parasitologia veterinaria, 2025)
Species of the chewing louse genus Neopsittaconirmus Conci, 1942 are host-specific parasites on Old World and Australasian parrots (Psittaciformes), infesting both wild and captive birds. Despite veterinarian practices that attempt to eliminate parasites from captive hosts, two species, Neopsittaconirmus gracilis Guimarães, 1974 and Neopsittaconirmus vendulae Sychra, 2006, frequently infest captive birds, not only their regular natural hosts, but also other species that are not naturally parasitized. Here we report and discuss additional records of these two species of lice from captive parrots in Brazil, Australia, England, Réunion and the United States of America.
Keywords: Parrots; Bird Diseases; nemoci ptáků; Animals, Zoo; Male; zavšivení; Animals; zvířata v ZOO; Lice Infestations; mužské pohlaví; ženské pohlaví; Female; zvířata; papouškovití; Ischnocera